2021
DOI: 10.3390/en14164746
|View full text |Cite
|
Sign up to set email alerts
|

Hot Compressed Water Pretreatment and Surfactant Effect on Enzymatic Hydrolysis Using Agave Bagasse

Abstract: Agave bagasse is a residual biomass in the production of the alcoholic beverage tequila, and therefore, it is a promising raw material in the development of biorefineries using hot compressed water pretreatment (hydrothermal processing). Surfactants application has been frequently reported as an alternative to enhance monomeric sugars production efficiency and as a possibility to reduce the enzyme loading required. Nevertheless, the surfactant’s action mechanisms in the enzymatic hydrolysis is still not elucid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…surface. [28] In the present investigation, water-soluble PEG 400 was selected as a non-ionic surfactant according to previous studies [29,43] and for the first time it was employed in combination with scCO 2 and FeCl 3 -catalysed scCO 2 . Moreover, in the perspective of the valorisation of sugar-rich hydrolysates obtained from the scCO 2 -catalysed hemicellulose hydrolysis via fermentation route, PEG 400 boosts the metabolic performance and the vitality of biocatalysts.…”
Section: Chempluschemmentioning
confidence: 99%
See 2 more Smart Citations
“…surface. [28] In the present investigation, water-soluble PEG 400 was selected as a non-ionic surfactant according to previous studies [29,43] and for the first time it was employed in combination with scCO 2 and FeCl 3 -catalysed scCO 2 . Moreover, in the perspective of the valorisation of sugar-rich hydrolysates obtained from the scCO 2 -catalysed hemicellulose hydrolysis via fermentation route, PEG 400 boosts the metabolic performance and the vitality of biocatalysts.…”
Section: Chempluschemmentioning
confidence: 99%
“…Hydrophobic interactions are the most influential on non-specific binding of cellulases onto lignin and humins surface. [29] Surfactants like PEG 400 are amphiphilic molecules that contain both hydrophilic and lipophilic groups that can reduce surface tension and help to remove hydrophobic molecules and modify the structure and surface of lignocellulosic biomass. [30] The role of PEG 400 can be explained by the modification of the structure of the biomass allowing greater accessibility to Cellic ® CTec3 HS enzymes, and by the reduction of the non-productive adsorption of the cellulase enzyme on lignin due to the preferential adsorption of the surfactant onto the exposed surface of lignin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome the non-productive absorption between lignin and cellulase for the improvement of enzymatic hydrolysis efficiency, additives such as non-ionic surfactants (e.g., Tween 80, Tween 20, and PEG), water-soluble lignin (e.g., lignosulfonate), and proteins (e.g., bovine serum albumin and soy protein) have been all proposed and tested. [19][20][21][22] These additives could be adsorbed by the surface lignin as well as the bulk residual lignin in the cell wall of pretreated biomass, thus blocking the non-productive adsorption between cellulase and lignin. 23 For example, Kapu et al found that the presence of PEG 6000 reduced the required cellulase loading by 77% and converted 97% of glucan and 44% of xylan in spent mushroom compost into monosaccharides.…”
Section: Introductionmentioning
confidence: 99%
“…, bovine serum albumin and soy protein) have been all proposed and tested. 19–22 These additives could be adsorbed by the surface lignin as well as the bulk residual lignin in the cell wall of pretreated biomass, thus blocking the non-productive adsorption between cellulase and lignin. 23 For example, Kapu et al found that the presence of PEG 6000 reduced the required cellulase loading by 77% and converted 97% of glucan and 44% of xylan in spent mushroom compost into monosaccharides.…”
Section: Introductionmentioning
confidence: 99%